A Systematic Literature Review On The Impact Of Toll Road Development To The Local Business On The Existing National Road - Alex Mahdi; Aceng Hidayat; Faroby Falatehan (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2024)
Development is a physical reality as well as a mental state (state of mind) of a society that has gone through a certain combination of socio-economic processes and institutions, has a way to create a better life. The development of toll roads is carried out to facilitate traffic in the regions, increase the efficiency and effectiveness of business especially on the distribution of goods and services. The purpose of this study is to review previous research related to the impact of toll road development on the socio-economic based on the SLR (Systematic Literature Review) method. Based on the results of the analysis obtained from 146 scientific journals that are relevant to the topic under study, previous studies stated that the toll road development impacted to the macro economic growth but in microlevel reduce the income of the business of the local community. The construction of the Toll Road in Lampung Province can contribute to the increase of macro-economic growth but in other hand decrease of the profit of the local business on the existing national road.